2022
DOI: 10.1186/s42825-022-00106-2
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping collagen-based nanoparticle with macrophage membrane for treating multidrug-resistant bacterial infection

Abstract: Nowadays, multidrug-resistant (MDR) bacterial infectious diseases has become a thorny issue in the healthcare field. Owning to its intrinsic merits, photodynamic therapy (PDT) shows tremendous strengths in fighting against MDR bacterial infections. However, most photodynamic nanoplatforms exhibit unsatisfactory targeting efficiency towards bacteria and infection site, which may compromise the bactericidal effect of PDT. Herein, we firstly reported a bacteria-targeted collagen-based nanoparticle, named Ce6/Col/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsbiomaterials.4c00056. Detailed experimental section; synthesis process, 1 H NMR spectrum, 13…”
Section: ■ Associated Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsbiomaterials.4c00056. Detailed experimental section; synthesis process, 1 H NMR spectrum, 13…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…aureus. , Due to the overuse and misuse of antibiotics and lack of new drug development, MRSA has increased dramatically throughout the world in recent decades and caused outbreaks and epidemics, leading to increased mortality. , According to statistics from the World Health Organization, 10 million people are expected to die from drug-resistant bacterial infections by 2050 . Therefore, in order to cope with the impending disaster caused by drug-resistant bacteria, it is urgent to seek and develop new therapeutic solutions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have combined macrophage membrane coating technology with photodynamic therapy (PDT) or photothermal therapy (PTT) to achieve targeted killing of pathogens [86,97,98]. For instance, Li and co-workers prepared a macrophage membrane coated with the photosensitizer chlorin e6 (Ce6/Col/MM) (figure 5(A)) [99]. They confirmed that CD14 on the Ce6/Col/MM surface enabled specific conjugation with MRSA (figures 5(B) and (C)).…”
Section: Inhibition and Killing Of Pathogensmentioning
confidence: 99%
“…Therefore, in the delivery system of methylene blue, the content of monomer state is improved by various methods, such as reducing the concentration, using surfactants, using liposomes and so on. [43][44][45] However, little attention is paid to the fact that whether methylene blue can maintain the monomer state with high photodynamic efficiency aer adsorption on the cell surface. In order to compare the possible mechanism of APDT of amphiphilic photosensitizer C 12 -MB, we studied the photosensitizer aggregation on the surface of bacterial cells by spectroscopy, and the results are shown in Fig.…”
Section: Photosensitizers Aggregation States Over Bacterial Cells Sur...mentioning
confidence: 99%